2008
DOI: 10.1109/tuffc.921
|View full text |Cite
|
Sign up to set email alerts
|

A composite high-frame-rate system for clinical cardiovascular imaging

Abstract: High frame-rate ultrasound RF data acquisition has been proved to be critical for novel cardiovascular imaging techniques, such as high-precision myocardial elastography, pulse wave imaging (PWI), and electromechanical wave imaging (EWI). To overcome the frame-rate limitations on standard clinical ultrasound systems, we developed an automated method for multi-sector ultrasound imaging through retrospective electrocardiogram (ECG) gating on a clinically used open architecture system. The method achieved both hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(32 citation statements)
references
References 46 publications
(41 reference statements)
0
32
0
Order By: Relevance
“…The quality of cardiac strain estimation can be increased using frame rates higher than those achieved by conventional imaging due to lower signal decorrelation [3]. Previous studies have shown that a higher frame rate can be achieved with methods such as multi-line acquisition [4, 5], multi-line transmit [6, 7], or ecg-gated acquisitions [8]. Multi-line transmit is prone to cross-talk artifacts and ecg-gated acquisitions can produce breathing or inconsistent heartbeats artifacts.…”
Section: Introductionmentioning
confidence: 99%
“…The quality of cardiac strain estimation can be increased using frame rates higher than those achieved by conventional imaging due to lower signal decorrelation [3]. Previous studies have shown that a higher frame rate can be achieved with methods such as multi-line acquisition [4, 5], multi-line transmit [6, 7], or ecg-gated acquisitions [8]. Multi-line transmit is prone to cross-talk artifacts and ecg-gated acquisitions can produce breathing or inconsistent heartbeats artifacts.…”
Section: Introductionmentioning
confidence: 99%
“…Of the two, it is often the decorrelation induced by very large strains that is more detrimental to strain estimation in cardiac applications. One particular focus of researchers for many years has been framerate, since the smaller inter-frame (incremental) strains imaged at higher framerates exhibit less RF signal decorrelation, and hence better motion estimation (Alam and Ophir, 1997; Chen et al, 2009; D’hooge et al, 2000; Hasegawa and Kanai, 2011; Wang et al, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…In the field of ultrasound elasticity imaging, numerous software beamforming techniques utilizing various transmit sequences have also been developed and implemented into commercial scanners to achieve high imaging rates and resolution such as composite imaging [55], plane-wave [56] or divergent transmit beam [57, 58]. High frame rate elasticity imaging has demonstrated a promising clinical value in quantitative imaging of tissue viscoelasticity with estimation of motion generated by external compression or acoustic radiation force such as Transient Elastography [59, 60], Shear Wave Imaging (SSI) [56, 61], Elastography [62], ARFI imaging [63], and Harmonic Motion Imaging [64].…”
Section: Introductionmentioning
confidence: 99%